2021
DOI: 10.1088/1361-6471/ac288b
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of N = 28 magicity in exotic 40Mg—probe of deformed halo and 2n-radioactivity at Mg neutron drip-line

Abstract: The exotic phenomenon of two-neutron halos and 2n-radioactivity are explored in the neutron-rich 40,42,44Mg by employing various variants of the relativistic mean-field approach. The extended tail of spatial density distributions including the enhanced neutron radii and skin thickness, pairing correlations, single-particle spectrum and wave functions predict 40,42,44Mg to be strong candidates for deformed neutron halos. Weakening of magicity at N = 28 plays a significant role in the existence of a weakly bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…This predominance reaffirms the significance of prolate deformation in the 2p-radioactivity as observed by Mukha et al [37]. Additionally, in the case of deformed nuclei, the occupancy in Nilsson orbital with the mixing of states near the Fermi level and the scattering of valence particles due to pairing correlations may contribute to a halo formation [83,84] with loosely bound pair of protons. With this in view, we look for the possible imprints of halo in the deformed nuclei listed in tables 1-3 by studying their charge radii and density profiles.…”
Section: Shape Coexistence and Halossupporting
confidence: 79%
“…This predominance reaffirms the significance of prolate deformation in the 2p-radioactivity as observed by Mukha et al [37]. Additionally, in the case of deformed nuclei, the occupancy in Nilsson orbital with the mixing of states near the Fermi level and the scattering of valence particles due to pairing correlations may contribute to a halo formation [83,84] with loosely bound pair of protons. With this in view, we look for the possible imprints of halo in the deformed nuclei listed in tables 1-3 by studying their charge radii and density profiles.…”
Section: Shape Coexistence and Halossupporting
confidence: 79%
“…2). After 1n-emission from 78 Ni * , the residual nucleus 77 Ni has much lower U th than in residual nucleus ( 79 Ni) of 80 Ni * . Lower U th results in lower NLD as is visible in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Another exotic decay, in which a heavy nucleus decays into a light daughter nucleus and emits a fragment, is named cluster-decay. This kind of decay was first studied by Sandulescu et al in 1980 [8] which is subsequently observed experimentally [9] in 223 Ra which decays into a large fragment near doubly-magic 208 Pb and a lighter [43][44][45] and several other clusters like 20 O, 22,24−26 Ne, 28−30 Mg, and 32,34 Si have been experimentally observed so far [46][47][48] which predominantly diverge towards Pb isotopes. Hence the emission of the cluster is closely related to the Pb isotopes in the heavy and superheavy regions which incited our investigation towards cluster emission.…”
Section: Cluster Decaymentioning
confidence: 84%
“…The commonly used variants are NL3 * [10], TMA [11], FSU-Gold [12], FSU-Garnet [13]. The relativistic mean-field approach and its variants are adequately described in various [12,[14][15][16][17][18][19][20] and our work [21] which can be referred for further details of the formalism. For comparison, the results of other theoretical models viz.…”
Section: Theoretical Frameworkmentioning
confidence: 99%